2021
DOI: 10.3389/fmicb.2020.619038
|View full text |Cite
|
Sign up to set email alerts
|

The Ribosome as a Switchboard for Bacterial Stress Response

Abstract: As free-living organisms, bacteria are subject to continuous, numerous and occasionally drastic environmental changes to which they respond with various mechanisms which enable them to adapt to the new conditions so as to survive. Here we describe three situations in which the ribosome and its functions represent the sensor or the target of the stress and play a key role in the subsequent cellular response. The three stress conditions which are described are those ensuing upon: a) zinc starvation; b) nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 143 publications
0
11
0
Order By: Relevance
“…This is a finding in line with a hypothesis that rRNAs play a central role in sensing stress. 38 The Helicase Sensor Identifies the Methyl Group Lost from m 4 C m during Stress. The hypermodified RNA m 4 C m stands out as one for further investigation because its levels decrease with both forms of stress studied.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…This is a finding in line with a hypothesis that rRNAs play a central role in sensing stress. 38 The Helicase Sensor Identifies the Methyl Group Lost from m 4 C m during Stress. The hypermodified RNA m 4 C m stands out as one for further investigation because its levels decrease with both forms of stress studied.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…Also, a significant loss of 30S/50S ribosomal proteins was observed at cold conditions. Numerous studies report that loss of ribosomal proteins in bacteria is the reaction to stress and is necessary for survival under nutrient- or energy-limited conditions 48,49,50,51 . GO analysis revealed that translation, gene expression, and protein folding were significantly affected at cold conditions (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…When bacteria are exposed to environmental stress, their ribosomes may act as either sensors, targets or responders to the change in conditions. A full discussion of the mechanisms underlying these processes is beyond the scope of this review and has already been described by Starosta et al (2014) and Cheng-Guang and Gualerzi (2021) so here we will focus on how ribosome profiling has contributed to understanding the interplay between ribosomes and cellular stress.…”
Section: Insights From Ribosome Profiling In Mycobacteriamentioning
confidence: 99%